Local history and landscape dynamics: A comparative study in rural Brazil and rural France. (February 2015) - Kohler, Florent; Marchand, Guillaume; Negrão, Marcelo
Highlights: Land use change is object of multi-agent models by social sciences. We explore the structural and proximate factors most cited in LCS literature. To this end, we draw a comparison between French and Brazilian rural land policies. Dynamics of deforestation and suburbanization are frequently based on local history. The concept of hysteresis helps us to highlight and overcome model inconsistencies. Abstract: In rural France as well as in rural Brazil, the years 1960–1970 were marked by profound socio-economic and environmental changes. In France, these changes were due to the agricultural modernization policy, in Brazil, they were caused mainly by the political integration of the Amazon to the rest of the country by infrastructure and agricultural colonization. The apparent irreversibility of the parallel phenomena of settlement, in France, and deforestation, in Brazil, gives us a comparative ground that this paper wishes to explore. We focused on four Brazilian protected areas and two French rural communes and studied the local attachment of the people and their collective attitude toward the environment. To do so, we assessed the main proximate factors identified in the literature, those determining the attitude of a human group toward its environment, an attitude influenced by structural drivers like legal issues and law enforcement. Our results suggest that these multiple factors are often randomly interconnected and can hardly be modeled. Land use and cover change may be an interesting way to understand social and environmental change, if accompanied by qualitative research about environmental and social perceptions. Our main conclusion is that collective and individual choices are eventually framed by local history: we use the notion of hysteresis to suggest that ancient causes may have enduring effects.